Upconversion luminescence of ytterbium and erbium co-doped gadolinium oxysulfate hollow nanoparticles. (December 2018) - Bian, Wenjuan; Zhou, Meng; Chen, Gen; Yu, Xue; Pokhrel, Madhab; Mao, Yuanbing; Luo, Hongmei
Graphical abstract: Abstract: Here we report the successful preparation of upconversion (UC) gadolinium oxysulfate (Gd2 O2 SO4 ) hollow nanoparticles with sensitizer Yb 3+ and activator Er 3+ co-doped through a biomolecule-assisted hydrothermal route and followed by calcination. By changing the experimnetal parameters, including the reaction temperature and surfactant type and concentration, the particle size and morphology can be regulated. Under the excitation of 980 nm laser, the red-to-green (R:G) emission intensity ratio is about 21:1, indicating the red emission color of 90%Gd2 O2 SO4 :9%Yb 3+, 1%Er 3+ hollow nanoparticles. The influence of the low temperature on luminescence is interpretated with enegy transfer mechanism. The red emission color and long lifetime at red emission regions enable their promising advanced luminescence microscopy applications.